Analysis of the application of the minimum quantity lubricant - MQL technique in the grinding process - da Silva, Leonardo Roberto; Bianchi, Eduardo Carlos [UNESP]; Fusse, Ronaldo Yoshinobu [UNESP]; França, Thiago Valle [UNESP]; Catai, Rodrigo Eduardo [UNESP]; Aguiar, Paulo Roberto [UNESP] (My University, 2007)
Conventional cutting fluids used in machining processes are problematic for manufacturers, since they pose serious health hazards to human health and to the environment. Environmental issues have become increasingly important in productive processes, ranking on a par with economic and technological aspects. This work, by L. R. da Silva, E. C. Bianchi, R. Y. Fusse, T. V. França, R. E. Catai and P. R. Aguiar, therefore focuses on the concept of minimum quantity of lubricant (MQL) in the grinding process. This technique has already been used successfully for many years in a variety of cutting processes. The grinding process involves several input parameters but, so far, little attention has been dedicated to the form and amount of cutting fluid applied in the process. The work reported on here involved an analysis of the behavior of the MQL technique, and the development of an optimized fluid application methodology consisting of a special nozzle through which a minimal amount of lubricant is pulverized through a compressed air flow. The evaluation of the performance of the MQL technique in grinding consisted of analyzing the behavior of the tangential cutting force, specific energy, G-ratio and roughness. It is expected that the results presented here will lead to technological and ecological gains in the grinding process using MQL.